Ketidakselarasan Pengaturan Keagenan Dalam Undang-Undang Cipta Kerja - Anisah, Siti (Jurnal Hukum IUS QUIA IUSTUM, 2025)
Agency relationships constitute a fundamental pillar of modern commerce. Large companies generally manage their corporate affairs through a series of agency activities, particularly in conducting their business operations. In Indonesia, however, the regulation of agency relationships is highly diverse. It can be said that the normative and academic understanding of agency law has not kept pace with regulatory developments responding to commercial activities. Therefore, this article examines the inconsistencies in the regulation of agency under the Job Creation Law and discusses their implications. To address this research focus, the author employs a normative legal research method. The study finds that the regulation of agency in the Job Creation Law is varied and inconsistent with the proper concept and legal framework that should apply to agents. The lawmakers appear not to have harmonized agency-related provisions across the various laws amended under the Job Creation Law as an omnibus law. Considering the significant role of agency in modern commercial life, there is a pressing need for a comprehensive legal framework that clearly regulates and properly positions agents in commercial transactions, thereby preventing overlaps in rights, obligations, authority, and responsibilities with principals and other intermediaries.